(3QbGHI GdHfc GdeQcRi GdeUQi Ydi GdGFJeGf GdeUQai h CKQg ai GdMO ef GdCReGJ GdeGdjI (B/ s - (3eMeO eMeO eMeO SdjeGfs; (3gGfi UdGM SQi GdOjf (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3fGbTJ GdQSGdI GdOhQ GdQbGHi ddHfc GdeQcRi GdeUQi Ydi GdHfhc h Ydi GdGFJeGf h Je YQV CSGdjH JhLjg GdHfc GdeQcRi GdeUQi ddGFJeGf GdeUQai deG ddGFJeGf GdeUQai ef OhQ aYGd ai NOeI GbJUGO GdOhdI(B. (3h Je YQV OhQGdHfc GdeQcRi CjVG ai ehGLgI GdCReGJ GdeGdjI deG dgPg GdCReGJ ef CKGQ Ydi GdHfhc h Ydi GdGbJUGO(B. (3h jeGQS GdHfc GdeQcRi egGeg ef NdGd fUhU bGfhf GdHfc GdeQcRi Qbe(B88 (3dSfI(B2003 (3h dGFMJg GdJfajPjI h Je GdJYdjb Ydi fUhU bGfhf GdHfc GdeQcRi h dGFMJg GdJfajPjI HGdTQM h JhVjM gOa GdeTQY efgG h edGMXGJ GdHGMK YdjgG(B. (3h GfJgJ GdQSGdI Edi eLehYI ef GdJhUjGJ JYdbJ HOhQ GdHfc GdeQcRi GdQbGHi Ydi YedjGJ efM GdGFJeGf h Ydi GdHfhc h YfO GdCReGJ GdeGdjIs
(3agQS(B: (3UaMGJ (B346-349.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQi (B2015.s
(3HHdjhLQGajG(B: (3UaMGJ (B339-345.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdHfc GdeQcRjs -- (3eUQs; (3GdGFJeGf GdeUQais; (3GdCReGJ GdeGdjIs; (3GdHfc GdeQcRi GdeUQis; (3GdGFJeGf GdeUQajs; (3GJaGbjI HGRds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs